2001
DOI: 10.1002/1616-5195(20010701)1:5<185::aid-mabi185>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Poly(γ-benzylL-glutamate)s Followed by Time-Resolved Emission Anisotropy

Abstract: Time-resolved emission anisotropy, r(t), of PBLG-A in (a) DMF, (b) THF and (c) 1,4-dioxane at a concentration of 10.0 g N l -1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…PBLG is known to form aggregates. [24] To further investigate the role of THF, PBLG‐based LLC phases in THF with biphenyl methanol‐ d 5 9 c as analyte were prepared. Temperature dependent 2 H NMR spectra clearly show a change of the quadrupolar splittings between 280 and 270 K, which is identical to the transition temperature T R already observed for PBPMLG phases investigated (see SI).…”
Section: Resultsmentioning
confidence: 99%
“…PBLG is known to form aggregates. [24] To further investigate the role of THF, PBLG‐based LLC phases in THF with biphenyl methanol‐ d 5 9 c as analyte were prepared. Temperature dependent 2 H NMR spectra clearly show a change of the quadrupolar splittings between 280 and 270 K, which is identical to the transition temperature T R already observed for PBPMLG phases investigated (see SI).…”
Section: Resultsmentioning
confidence: 99%
“…As fluorescence (FL) spectroscopy constitutes one of the most powerful tools to study the aggregation of polymers, traditional fluorescent probes such as carbazolyl, 17 dansyl, 18 and pyrene 19 have been chemically incorporated with poly(γbenzyl-L-glutamate) (PBLG) to monitor the chain conformations of PBLG in solution. For example, the absence of excimer emission in the pyrene-labeled poly(ethylene glycol)-b-PBLG 19 indicated that the pyrene groups were separated from each other in the self-assembled structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…PBLG is known to form aggregates [24] . To further investigate the role of THF, PBLG‐based LLC phases in THF with biphenyl methanol‐ d 5 9 c as analyte were prepared.…”
Section: Resultsmentioning
confidence: 99%
“…www.angewandte.de PBLG is known to form aggregates. [24] To further investigate the role of THF, PBLG-based LLC phases in THF with biphenyl methanol-d 5 9 c as analyte were prepared. Temperature dependent 2 H NMR spectra clearly show a change of the quadrupolar splittings between 280 and 270 K, which is identical to the transition temperature T R already observed for PBPMLG phases investigated (see SI).…”
Section: Angewandte Chemiementioning
confidence: 99%